Stereochemistry of two pheromonal components of the bumblebee wax moth, Aphomia sociella - Wallin, Erika A; Kalinová, Blanka; Kindl, Jiří; Hedenström, Erik; Valterová, Irena (Scientific reports, 2020)
The bumblebee wax moth, Aphomia sociella, is a parasite of bumblebees. In this species, males produce sexual pheromone to attract females, while females produce an aphrodisiac pheromone that initiates male courtship. Both pheromones contain 6,10,14-trimethylpentadecan-2-one (TMPD-one) and the corresponding alcohol, 6,10,14-trimethylpentadecan-2-ol (TMPD-ol) in sex specific quantities. Male sex pheromone consists of 7 components with TMPD-one as a minor one and traces of TMPD-ol. In female aphrodisiac pheromone, TMPD-ol is the major component, while TMPD-one is present in traces. Here we report on the absolute configuration of TMPD-one in male sex pheromone and TMPD-ol in female aphrodisiac pheromone of A. sociella. The configuration was determined from GC/MS of prepared (S)-acetoxypropionyl esters of TMPD-ol. TMPD-one was first reduced to the alcohol that was then derivatized with (S)-acetoxypropionyl chloride. The GC/MS data of obtained diastereoisomers were compared with synthetic standards. The absolute configuration of TMPD-one in the male pheromone was (6R,10R). The configuration of TMPD-ol in the female pheromone was (2R,6R,10R). Electrophysiological experiments showed that TMPD-one and TMPD-ol are perceived by both sexes. The synthetic standards of naturally produced stereoisomers elicited higher responses than mixtures of all stereoisomers.
Keywords: ženské pohlaví; plynová chromatografie s hmotnostně spektrometrickou detekcí; můry; Female; sexuální lákadla; Animals; Sex Attractants; Gas Chromatography-Mass Spectrometry; Male; Stereoisomerism; mužské pohlaví; zvířata; stereoizomerie; Moths